UVSSA, UBP12, and RDO2/TFIIS Contribute to Arabidopsis UV Tolerance - Al Khateeb, Wesam M.; Sher, Annan A.; Marcus, Jeffery M.; Schroeder, Dana F. (Frontiers in Plant Science, 2019)
Plant DNA is damaged by exposure to solar radiation, which includes ultraviolet (UV) rays. UV damaged DNA is repaired either by photolyases, using visible light energy, or by nucleotide excision repair (NER), also known as dark repair. NER consists of two subpathways: global genomic repair, which repairs untranscribed DNA throughout the genome, and transcription-coupled repair (TCR), which repairs transcribed DNA. In mammals, CSA, CSB, UVSSA, USP7, and TFIIS have been implicated in TCR. Arabidopsis homologues of CSA (AtCSA-1/2) and CSB (CHR8) have previously been shown to contribute to UV tolerance. Here we examine the role of Arabidopsis homologues of UVSSA, USP7 (UBP12/13), and TFIIS (RDO2) in UV tolerance. We find that loss of function alleles of UVSSA, UBP12, and RDO2 exhibit increased UV sensitivity in both seedlings and adults. UV sensitivity in atcsa-1, uvssa, and ubp12 mutants is specific to dark conditions, consistent with a role in NER. Interestingly, chr8 mutants exhibit UV sensitivity in both light and dark conditions, suggesting that the Arabidopsis CSB homologue may play a role in both NER and light repair. Overall our results indicate a conserved role for UVSSA, USP7 (UBP12), and TFIIS (RDO2) in TCR.